Analysis of Postponement Practice in Cement Supply Chain: A Case Study - Fauzan Romadlon; Hadi Kurniawan; Ridho Ananda (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2020)
This research focuses on assessing implementing postponement in a cement industry especially for OPC (Ordinary Portland Cement) in Indonesia. The company offers three postponement points; Ciawi and Kampung Rambutan, and Jatiwarna. This research has been done with observational method to map customer condition. Moreover, implementing linear programming model is used to gain optimal solution for allocated truck. The results are, highest proportion of OPC customer is in Jakarta, followed Karawang, and Bogor. The result from linear programming model simulation, Ciawi point is assigned to serve Jakarta and Bogor’ customers, Kampung Rambutan point is assigned for Jakarta and Kawarang’ customers, and Jatiwarna point is prepared for Jakarta, Karawang, Bekasi, Lampung, Pekalongan, Tangerang, and Serang’ customers. So, implementing postponement can increase customer satisfaction without adding higher cost such as investment cost. The cement industry encounter effectiveness and responsiveness even tough, some problem shall be taken such as double administration process (manual and computerized).